Large-scale synthesis of low-cost bimetallic polyphthalocyanine for highly stable water oxidation - Qi, Qianglong; Hu, Jue; Guo, Sitian; Song, Hongchuan; Wang, Shixing; Yao, Yaochun; Le, Thiquynhxuan; Li, Wei; Zhang, Chengxu; Zhang, Libo (Applied catalysis. B, Environmental, 2021)
FeCo-bimetallic polyphthalocyanine (FeCo-PPc) with ultra-low cost and excellent oxygen evolution reaction (OER) electrocatalytic performance has been prepared in kilogram-scale. The FeCo-PPc shows excellent long-term stability under an industrial hydrogen production condition (6 M KOH and 85℃). [Display omitted] •FeCo-PPc with low cost of less than $0.1/g and excellent OER electrocatalytic performance prepared in kilogram-scale for the first time.•Only an overpotential of 308 mV to deliver a current density of 500 mA cm−2.•The overpotential after the stability test increased only 3 mV at the current density of 100 mA cm−2 for 24 h.•Outstanding long-term stability under 6 M KOH and 85℃ at the high current densities of 100 mA cm−2 and 500 mA cm−2. Although large-scale synthesis of inexpensive and efficient electrocatalysts for oxygen evolution reaction (OER) is critical for industrial water splitting, little attention has been paid to that. Here, FeCo-bimetallic polyphthalocyanine (FeCo-PPc) with ultra-low-cost of less than $0.1 per gram and excellent OER electrocatalytic performance has been prepared in kilogram-scale for the first time. The FeCo-PPc catalyst, around 1/5000th times lower the cost of the commercial IrO2, exhibits 24 times higher turnover frequency (0.417 s−1 at 300 mV) and much lower the overpotential (308 mV at 500 mA cm−2) than that of IrO2 (0.0177 s−1 and 588 mV, respectively). Moreover, the FeCo-PPc catalyst shows outstanding long-term stability under an industrial condition (6 M KOH and 85℃) at the high current densities of 100 mA cm−2 and 500 mA cm−2. The excellent OER activity can be attributed to the electron interaction between Fe and Co and the electronegativity of N atoms, which regulate the electron cloud density of neighboring atoms and form active sites to promote the adsorption of reactants. Our work may guide rational design and large-scale synthesis of electrocatalysts that work well at high current densities in industrial conditions.